INDIKASI PENYALAHGUNAAN POSISI DOMINAN PADA MERGER PERUSAHAAN DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA (Studi Pada Merger PT Aplikasi Karya Anak Bangsa dan PT Tokopedia) - Syifa Addini Humairah (2022)
The focus of this study is indications of abuse of dominant position as a result of the merger carried out by decacorn and unicorn companies Gojek and Tokopedia. In the business competition law in Indonesia, if the merger transaction creates an unfair business competition climate, the merger transaction is prohibited. KPPU has the authority to evaluate the notification given, but the notification that is currently enforced is a post-merger notification which is not in line with the current requirements of Indonesian business competition law. Although Article 47 of the Antimonopoly Law states that KPPU can cancel a merger, KPPU has never canceled a merger. This study uses normative legal research methods with data collection methods in the form of library research. As an effort to prevent unfair business competition arising from a merger, it is necessary to implement a pre-merger notification. The digital economy industry tends to have a structure that leads to a contestable market, but it is feared that companies that want to enter the same market have insecurity about the success of their business. Therefore, regulations are needed that can accommodate business competition in the digital sector.